2019
DOI: 10.3390/nu11122912
|View full text |Cite
|
Sign up to set email alerts
|

Apple Preload Halved the Postprandial Glycaemic Response of Rice Meal in Healthy Subjects

Abstract: This study aimed to investigate the possible glycemic effect of apple preload on acute postprandial glycemic responses (GRs) of a following rice meal, comparing with its co-ingestion counterpart and an apple sugar solution preload, based on equal carbohydrates intake. In a randomized crossover trial, 18 healthy female subjects consumed (1) rice, (2) co-ingestion of apple and rice (A+R), (3) apple preload and rice (PA+R), and (4) rice with sugar solution preload (same sugar profile as in apple) (PSS+R). Acute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…(2) with a body mass index (BMI) between 18.5 and 23.9 kg/m 2 ; (3) weight stable (±2 kg) within the last six months; (4) not on diet to gain or to lose weight in the past three months; (5) The sample size calculation was done with the PASS 13 Power Analysis and Sample Size software (NCSS, Kaysville, UT, USA). Assuming that the standard deviation (SD) is lower than 55.15 mmol•min/L, a sample size of n = 11 provided 80% power to detect a change of 167.8 mmol•min/L in iAUC (p < 0.05), based on our previous study [16].…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…(2) with a body mass index (BMI) between 18.5 and 23.9 kg/m 2 ; (3) weight stable (±2 kg) within the last six months; (4) not on diet to gain or to lose weight in the past three months; (5) The sample size calculation was done with the PASS 13 Power Analysis and Sample Size software (NCSS, Kaysville, UT, USA). Assuming that the standard deviation (SD) is lower than 55.15 mmol•min/L, a sample size of n = 11 provided 80% power to detect a change of 167.8 mmol•min/L in iAUC (p < 0.05), based on our previous study [16].…”
Section: Subjectsmentioning
confidence: 99%
“…Moreover, increasing epidemiological studies and meta-analyses have reported that daily consumption of fruit has relevance to a lower incidence of type 2 diabetes [24][25][26][27][28]. It is reported that partial substitution of white rice with certain fruits or dried fruits improved PGRs [16,29,30] and HbA1c levels [31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of practicable postprandial glycemic attenuating strategies, preliminary studies indicated that preload interventions resulted in curbed glycemic excursion as well as favorable insulin and gut hormone responses [3,4]. In addition to the protein preload, previous studies suggested that the preload of carbohydrate-rich food, such as rice [5], fruits [5,6], and sugar solution [6], could yield more stable postprandial glycemic responses (GRs) compared with their non-preload counterparts.…”
Section: Introductionmentioning
confidence: 99%